Den gode sædcelle... En antropologisk analyse af arbejdet med sædkvalitet. - Mohr, Sebastian; Høyer, Klaus (K&K - Kultur og Klasse, 2012)
THE GOOD SPERM CELL … | Questions about who has the right to be pregnant, and with whom, and which children should be allowed to be born are fundamentally political and normative. However, when fertilization involves reproductive tech nologies these normative questions are often translated into questions of quality whereby they come to appear technical. This becomes clear in the work to ensure “good sperm quality”. Sperm quality is measured both at a population level, in connection to fertility treatment of infertile men, in the recruitment of sperm donors and in connection with attempts to produce so-called artificial sperm. What is regarded as good quality is not only based on “medical evidence” but also on beliefs about what is wished for and what is not. Put differently, medical evidence is produced in light of specifically desired outcomes. This article asks how one determines sperm quality and what kind of practices and normative choices this evaluative process involves. The article builds on medical literature, fieldwork at both a laboratory dealing with sperm analysis and at sperm banks and on interviews with scientists working on the development of artificial sperm.